THE EFFECT OF GOVERNANCE ON RISK RATING (CASE STUDY ON ESG INDEXED BANKS PERIOD 2021-2022) - Euis Yunita Purnama Sari; Estu Widarwati (ACCRUALS (Accounting Research Journal of Sutaatmadja), 2024)
The global economy still affects the performance of the banking industry to date. However, economic and banking conditions this year are better compared to the previous year as global pressures begin to ease. Banking must be managed as much as possible in order to always obtain profits and avoid all forms of losses. Losses experienced by banks can affect the health of the bank itself. This study aims to examine the effect of governance on risk rating. In this study the independent variable is governance measured by ownership while for the dependent variable in this study is risk rating measured by ESG Score, and bank size measured by total assets The sample in this study is the state-owned bank listed in the ESG Index 2021-2022. The sampling technique uses the purposive sampling method, and produces 4 bank as samples. Linier regression used to test the hyphotesis. The results showed that governance had no positive effect on the risk rating. Although not strong evidence of governance impact to risk rating, a bank should concern to manage it activities that keep stable of risk rating